Problems of Islamic Education Curriculum in Indonesia - Deny Ahmad Jaelani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The curriculum can be interpreted as a number of subjects that must be taken by students to get a diploma. The curriculum consists of several components, namely the objective component, material component, material component, strategy component and evaluation component. The problems of the Islamic education curriculum that are often encountered in Indonesia are (1) The curriculum content is the same as schools, only madrasas still leave their Islamic characteristics with religious subjects, which are not as strong and deep as they were at the beginning of its formation. less interesting in terms of material and delivery methods used. The design of the Islamic education curriculum is very much dominated by normative, ritual, and eschatological issues. If you pay attention to the design of Islamic education curriculum programs from elementary/MI to university levels, it is felt that they have not been able to answer the challenges of change, because the Islamic education curriculum focuses more on focuses on the correspondence-textual aspect, which emphasizes the memorization of existing religious texts. The reality found in the field is that the assessment of learning outcomes is more referred to as an individual assessment which emphasizes the cognitive aspect, and uses the form of Islamic religious exam questions that are more comprehensive. shows the main priority in the cognitive aspect as well, and rarely does the question have a functional spiritual "value" and "meaning" of religious spirituality in everyday life, 90% of madrasas are managed by the community (private) with different qualification levels in various aspects, due to limited facilities and infrastructure owned by madrasas, the preparation and development of the curriculum so far, it turns out that the burden is more on the madrasah principal and teachers, the involvement of madrasah committees, foundations and the community is still relatively small, in fact it almost does not happen.